Optimizing Pathological Examination Cost Control Through Process Management Information Systems: A Mixed-Methods Study - Huang Q; Jiang W; He Y; Wang W; Song B (Risk Management and Healthcare Policy)
Qin Huang,1,2 Wei Jiang,1,2 Ying He,1,2 Wei Wang,1,2 Bo Song1,2 1Department of Pathology, West China Second University Hospital, Sichuan University, Chengdu, Sichuan, People’s Republic of China; 2Key Laboratory of Birth Defects and Related Diseases of Women and Children (Sichuan University), Ministry of Education, Chengdu, Sichuan, People’s Republic of ChinaCorrespondence: Wei Jiang; Wei Wang, Department of Pathology, West China Second University Hospital, Sichuan University, No. 20 section 3, South Renmin Road, Chengdu, Sichuan, 610041, People’s Republic of China, Email 756267990@qq.com; bearwin2000@126.comBackground: This study aimed to investigate the effects of process management information systems used for consumable management in the Department of Pathology.Methods: Data, such as workload capacity of each work group from 2022 to 2023, consumable consumption, warehouse receiving and dispatching, and price of consumables, were extracted from the hospital information system (HIS) and the Goldisc Picture Archiving and Communication System (PACS) of West China Second University Hospital, Sichuan University. Chi-square test and 95% confidence interval (CI) analysis were performed to assess the effects of the systems in optimizing pathological examination cost control. The focus group interviews were conducted to investigate the advantages, limitations and optimization strategy of the systems.Results: The workload capacities of the cellular pathology group, molecular pathology group, frozen section group, immunohistochemistry group, and routine pathological examination group increased by 20.17%, 22.72%, 24.10%, 24.28%, and 20.11%, respectively (P < 0.0001) (95% CI: 19.74%, 24.81%). The difference in the quantity of medical consumables received at the warehouse between 2022 and 2023 was 148,975 (P < 0.0001). The difference in the quantity of dispatched medical consumables between 2022 and 2023 was 150,282 (P < 0.0001). The overstock inventory of medical consumables decreased from 996,527.33 (Chinese Yuan) for 2022 to 832,401.60 (Chinese Yuan) for 2023. The quantity of waste in glass slides decreased from 17,244 for 2022 to 1,538 for 2023 (P < 0.0001). The timeliness rate of histopathological diagnosis in 2023 increased from 65.07% (data for 2022) to 95.46%. The timeliness rate of intraoperative pathological rapid diagnosis in 2023 increased from 67.34% (data for 2022) to 89.45%.Conclusion: Intelligent information management modules should be configured for medical consumables to optimize the allocation of medical resources and reduce the cost of pathological examinations. The process management information systems could significantly optimize pathological examination cost control.Keywords: cost control, information management, materials management, pathology department, hospital